FUNDING STRATEGIES FOR ENHANCING THE OPERATIONS OF SMALL AND MEDIUM SCALE BUSINESSES FOR SUSTAINABILITY IN ENUGU STATE - Ozor, Stephen Chukwuemeka (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
The study determined the funding strategies for enhancing the operations of small and medium scale businesses for sustainability in Enugu State. Survey research design was used for the study. One research question was answered and one null hypothesis tested at 0.05 level of significance. The population of the study was 1,432 registered small and medium scale enterprises in Enugu State. The sample size of 313 was drawn from the population using Yaro Yamane formula. The instrument used for data collection was structured questionnaire. The instrument was validated by three experts, two from Business Education Department and one from Measurement and Evaluation Department all from Enugu State University of Science and Technology. The reliability of the instrument was determined by using cronbach Alpha correlation co-efficient and a reliability index of 0.773 was obtained which showed that the instrument was reliable. Only 225 copies of the questionnaire distributed were returned, 140 copies from the Urban Areas and 85 Copies from the Rural Areas. Mean and standard deviation were used to answer the research question while t-test was used to test the hypothesis at 0.05 level of significance. Among the findings of the study were that starting with personal savings, borrowing from commercial banks, Sourcing grants from International Collaborative Partners and employment of financial experts to give professional touch to the management of finances are some of the funding strategies for enhancing the operations of SMEs for sustainability. Some of the recommendations made were that, SME in Enugu should explore funding opportunities available locally and internationally to raise fund for SMEs sustainability and that SME operators in Enugu State should acquire relevant financial management skills before embarking on SMEs operation.